2017
DOI: 10.1002/slct.201701911
|View full text |Cite
|
Sign up to set email alerts
|

Calcination‐Dependent Morphology Transformation of Sol‐Gel‐ Synthesized MgO Nanoparticles

Abstract: Sol‐gel synthesis is a widely accepted method of producing nanoparticles with high surface area‐to‐volume ratio and purity at relatively low temperatures. For metal oxide nanoparticle synthesis, sol‐gel maintains a good metal oxide composition with controlled chemical structure and the ability to fine‐tune morphology and size. Magnesium oxide (MgO) nanoparticles possess unique physicochemical characteristics that have enabled a wide range of applications from catalysis to disease treatment. The potential featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 102 publications
2
19
0
Order By: Relevance
“…Jeevanandam et al [ 33 ] reported the presence of negatively charged oxide ions on the surface of MgO nanoparticles ranging from −11.4 to −21.4 mV. Since a similar synthesis method is used in this study, MgO nanoparticles are assumed to a possess negative charge.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Jeevanandam et al [ 33 ] reported the presence of negatively charged oxide ions on the surface of MgO nanoparticles ranging from −11.4 to −21.4 mV. Since a similar synthesis method is used in this study, MgO nanoparticles are assumed to a possess negative charge.…”
Section: Resultsmentioning
confidence: 98%
“…The thermal degradation and calcination temperature used to obtain spherical‐shaped MgO nanoparticles were adapted from our previous study. [ 33 ] The flowchart for the sol‐gel couple ultrasonication synthesis of the MgO nanoparticles is illustrated in Figure 1. All the equipment involved in this experiment was cleaned thoroughly beforehand to prevent any contamination during sample preparation.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al demonstrated that the Li doping could increase the concentration of surface defect, enhance the basicity of nanoplates, and then improve antibacterial activity of MgO . Furthermore, studies showed that calcination temperature played a key role in the size and crystallinity of MgO . High calcination temperatures ( T calc ≥700 °C) can change the defect properties of micro‐rod MgO and improve its antimicrobial activity .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Furthermore, studies showed that calcination temperature played a key role in the size and crystallinity of MgO. [12] High calcination temperatures (T calc � 700°C) can change the defect properties of micro-rod MgO and improve its antimicrobial activity. [13] However, there is few report that study the effect of calcination temperature on surface defect and antibacterial activity of MgO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%